Desempenho agronômico do híbrido de milho pipoca IAC 125 submetido a diferentes densidades de plantas e lâminas de água - Stipp, Oelcio José (2016)
The objective was to verify the influence of plant density and irrigation depths on popping expansion and agronomic traits in the popcorn hybrid IAC125 in two growing seasons (2014/15 and 2015/16), in Maringá, PR. Each treatment was represented as combination of two factors arranged in a split split-plot design. The factors were represented by population density with five levels (40000, 55000, 70000, 85000 and 100000 plants ha-1) and irrigation depths with five levels (574.86 (without irrigation); 609.86; 644.86; 679.86 (control) and 714.86 mm) at the growing season 2014/15 and (857.4 (without irrigation); 867.26; 886.60; 916.78 (control) and 959.81), at the growing season 2015/16, with six replications. The field experiments carried out in randomized block design with treatments arranged in a split plot scheme. In addition, the population density was considered as principal treatment randomized at each plot, the irrigation depths was taken as the sub-treatment at the split-plot. The traits evaluated were: plant height, height of ear insertion, stem diameter, number of lodged and broken plants, ear diameter, ear length, number of rows per ear, number of kernels per row, weight of thousand grain, grain yield and popping expansion. Our results did not show significant interaction between population density and irrigation depths effect, suggesting that both factors are independentl in relation to all agronomic traits evaluated. In both growing seasons a significant linear increase effect for grain yield in function of population density and irrigation depths was observed. Population density and depths of irrigation not showed effect on popping expansion (P>0.05) in both growing seasons (2014/15 and 2015/16).